Adventures in arduino - Stewart, Becky (Adventures In, 2015)
Arduino programming for the absolute beginner, with project-based learning Adventures in Arduino is the beginner's guide to Arduino programming, designed specifically for 11-to 15-year olds who want to learn about Arduino, but don't know where to begin. Starting with the most basic concepts, this book coaches you through nine great projects that gradually build your skills as you experiment with electronics. The easy-to-follow design and clear, plain-English instructions make this book the ideal guide for the absolute beginner, geared toward those with no computing experience. Each chapter includes a video illuminating the material, giving you plenty of support on your journey to electronics programming. Arduino is a cheap, readily available hardware development platform based around an open source, programmable circuit board. Combining these chips with sensors and servos allows you to gain experience with prototyping as you build interactive electronic crafts to bring together data and even eTextiles. Adventures in Arduino gets you started on the path of scientists, programmers, and engineers, showing you the fun way to learn electronic programming and interaction design. -Discover how and where to begin Arduino programming -Develop the skills and confidence to tackle other projects -Make the most of Arduino with basic programming concepts -Work with hardware and software to create interactive electronic devices There's nothing like watching your design come to life and interact with the real world, and Arduino gives you the capability to do that time and again. The right knowledge combined with the right tools can create an unstoppable force of innovation, and your curiosity is the spark that ignites the flame. Adventures in Arduino gets you started on the right foot, but the path is totally up to you.